SYSTEMATIC LITERATURE REVIEW: PENGARUH KOMUNIKASI DAN OCB TEHADAP KINERJA KARYAWAN - Mohammad Hakim Maulana; Nur Hidayah Isnaeni; Vivi Anistyaningrum; Dani Rizana (Cahaya Ilmu Bangsa, 2025)
This research aims to explore the influence of communication and Organizational Citizenship Behavior (OCB) on employee performance in an organizational context. Employees as strategic assets not only carry out their duties, but also contribute to innovation and a positive work culture. In an era of intense competition, it is important for companies to manage employees with a humanistic approach that includes development and empowerment. Employee performance, which reflects individual effectiveness in completing tasks, is influenced by various factors including effective communication and OCB behavior. Through Systematic Literature Review (SLR), this research analyzes related literature to understand the relationship between these variables. Results show that good communication increases job satisfaction, which in turn has a positive impact on performance. Additionally, OCB behavior contributes to organizational success by increasing collaboration and harmony in the workplace. This research concludes that companies need to expend resources in communication and OCB development to achieve competitive advantage.